Hierarchical, virtualised and distributed intelligence 5G architecture for low‐latency and secure applications. Issue 9 (22nd July 2016) - Siddiqui, M.S.; Legarrea, A.; Escalona, E.; Parker, M.C.; Koczian, G.; Walker, S.D.; Lyberopoulos, G.; Theodoropoulou, E.; Filis, K.; Foglar, A.; Ulbricht, M.; Liu, Y.; et al.
Abstract: CHARISMA aims to tackle low‐latency and end‐to‐end security for converged fixed/wireless 5G networks in order to meet the complex demands of emerging business paradigms, such as Smart Cities, eHealth and Industry 4.0. In this paper, we present the key drivers and requirements towards a hierarchical, distributed‐intelligence 5G architecture, supporting low latency, security and open access as features intrinsic to its design. We also investigate the business perspective of the proposed 5G solution and the changes that can be foreseen for the telecom ecosystem. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Converged heterogeneous advanced 5G cloud‐RAN architecture for intelligent and secure media access aims to tackle low‐latency and end‐to‐end security for converged fixed/wireless 5G access networks. In this paper, we present the key drivers and requirements towards a hierarchical, distributed‐intelligence 5G architecture, supporting low latency, security, and open access as features intrinsic to its design. We also investigate the business perspective of the proposed 5G solution and the changes that can be foreseen for the telecom ecosystem.